History of Lahore in Urdu prose literature - Dr. Rehana Kausar; Prof Dr Muhammad Kamran (Zaban-o-Adab, 2025)
Lahore, the city of lights and colors, has its own very diverse and rich historical and cultural values. Lahore, the capital of Punjab, went through various ages during its cultural and civilization evolution. There are many things found in history about its settlement and name. Ancient Lahore that settled on the bank of the river Ravi has still its monuments and remnants of the ancient city. It has many famous and historical places. The Mughal architecture has its own magnificent impact and shows beauty and glory of Mughal reign. Lahore city has always been important, and core center in terms of development and industrial context. During the Sikh era, Lahore’s civilization suffered through many destructions and decline. In the British era, the civilization of Lahore enlightened by new horizons of development. Urdu prose depicts different ages and shades of Lahore. In this article an attempt has been made to review the history of Lahore in the light of Urdu literature.